2020
DOI: 10.1093/jas/skaa081
|View full text |Cite
|
Sign up to set email alerts
|

Satellite cells and their regulation in livestock

Abstract: Satellite cells are the myogenic stem and progenitor population found in skeletal muscle. These cells typically reside in a quiescent state until called upon to support repair, regeneration, or muscle growth. The activities of satellite cells are orchestrated by systemic hormones, autocrine and paracrine growth factors, and the composition of the basal lamina of the muscle fiber. Several key intracellular signaling events are initiated in response to changes in the local environment causing exit from quiescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 119 publications
0
13
0
Order By: Relevance
“…The intramuscular region, however, is the last depot for adipogenesis in growing cattle (Oliveira et al, 2011), and the puberty process is likely more influenced by subcutaneous fat accretion ( Lammoglia et al, 2000 ; Garcia et al, 2002 ; Roberts et al, 2017 ). In turn, myogenic factors are downregulated as cattle mature and muscle fibers are fully developed ( Picard et al, 2002 ; Du et al, 2010 ); hence, treatment differences noted for mRNA expression of myogenin and PAX7 in the LM (day 584) may be indicative of hastened physiological maturation in heifers from AAC cows ( Gonzalez et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The intramuscular region, however, is the last depot for adipogenesis in growing cattle (Oliveira et al, 2011), and the puberty process is likely more influenced by subcutaneous fat accretion ( Lammoglia et al, 2000 ; Garcia et al, 2002 ; Roberts et al, 2017 ). In turn, myogenic factors are downregulated as cattle mature and muscle fibers are fully developed ( Picard et al, 2002 ; Du et al, 2010 ); hence, treatment differences noted for mRNA expression of myogenin and PAX7 in the LM (day 584) may be indicative of hastened physiological maturation in heifers from AAC cows ( Gonzalez et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, when the BSCs were induced to differentiate, PAX7 mRNA abundance increased 2 h post-induction, and then proceeded to decrease in abundance. One possible explanation for this is that satellite cells are a heterogeneous population, with a portion of cells remaining in reserve and proliferating, not differentiating [ 8 ]. Additionally, the compounds used in this study have been found to increase proliferation rates of BSCs [ 25 ], and therefore it would not be surprising if some of the cells remained in a proliferative phase initially when being induced to differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Satellite cells are muscle precursor cells that proliferate, then differentiate and fuse into myotubes or with existing muscle fibers to support hypertrophy [ 5 ]. Differentiation and phenotypic maturation are necessary for satellite cells to fuse [ 8 ]. Markers of differentiation in skeletal muscle include increased expression of myogenic differentiation factor 1 (MyoD ), myogenic factor 5 ( Myf5 ), and myogenin, and decreased expression of paired box transcription factor 7 ( Pax7 ) [ 6 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc is vital to cellular proliferation [26] and is a cofactor to metalloproteinases 2 and 9 [27], both of which are associated with increased proliferation rates [11], and protein turnover [10] in bovine satellite cells. Satellite cells are essentially muscle precursor cells [28] and are required to support skeletal muscle hypertrophy. Increasing satellite cell numbers allows for an increased capacity for skeletal muscle growth to occur [29].…”
Section: Discussionmentioning
confidence: 99%